SFRP4+IGFBP5hi NKT cells induced neural-like cell differentiation to contribute to adenomyosis pain - Chen, Yichen; Zhu, Jue; Chen, Liang; Shen, Yuanyuan; Zhang, Jing; Wang, Qiming (Frontiers in Immunology, 2022)
Adenomyosis is an estrogen-dependent gynecological disease. The pathogenesis of chronic pain, the main clinical symptom of adenomyosis, remains undefined. As a combination lymphocyte with both T-cell and NK-cell properties, NKT cells play a role in immune defense against numerous diseases and modulate cell differentiation. This study analyzed tissue-cell samples from adenomyosis with or without pain by single-cell sequencing. We found a specific population of SFRP4+ NKT cells and a large amount of undifferentiated multipotent stem cells in the adenomyosis pain group. We discovered that high expression of IGFBP5 in SFRP4+NKT cells could promote the differentiation of multipotent stem cells into neural-like cells via the single cell trajectory. Verification by sample, the degree of expression of neuronal marker NEFM correlated with duration of pain in adenomyosis patients. The expression of IGFBP5 was positively correlated with the pain scores of adenomyosis patients. Collectively, these findings suggest SFRP4+IGFBP5hi NKT cells were capable of converting part of the stem cells into neurogenic cells and inducing adenomyosis pain.